2002
DOI: 10.1051/lait:2002045
|View full text |Cite
|
Sign up to set email alerts
|

Determination of lactulose and furosine in milk using front-face fluorescence spectroscopy

Abstract: -A novel rapid and non-destructive front-face fluorescence method to quantify furosine and lactulose in heat-treated milk has been developed. The emission fluorescence spectra (305-450 nm) of tryptophans of proteins, and emission and excitation fluorescence spectra of fluorescent Maillard-reaction products were recorded directly on milk samples. Principal component analysis (PCA) and principal component regression (PCR) were applied to process the spectra obtained. The front-face fluorescence method can give v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 21 publications
5
61
0
1
Order By: Relevance
“…Advanced Maillard products and Soluble Tryptophan) have been used to evaluate the progress of Birlouez-Aragon, 2001;Kulmyrzaev & Dufour, 2002;Birlouez-Aragon, Sabat & Gouti, 2002;Gliguem & Birlouez-Aragon, 2005;Guan, Liu, Ye & Yang, 2005) and infant formulas (Ferrer et al, 2000;Birlouez-Aragon et al, 2004;Birlouez-Aragon, Locquet, Louvent, Bouveresse & Stahl, 2005). However, studies on the effects of storage on the formation of fluorescent compounds in infant formulas (Ferrer, Alegría, Farré, Clemente & Calvo, 2005) and milks (Gliguem et al, 2005; Birlouez-Aragon, Sabat, Lutz, Leclère & Nicolas, 1999) are scarce, and there is a lack of reports on the formation of MR products in infant foods, as a consequence of either processing or storage.…”
Section: Measurements Of Fluorescence At Different Wavelengths or Thementioning
confidence: 99%
“…Advanced Maillard products and Soluble Tryptophan) have been used to evaluate the progress of Birlouez-Aragon, 2001;Kulmyrzaev & Dufour, 2002;Birlouez-Aragon, Sabat & Gouti, 2002;Gliguem & Birlouez-Aragon, 2005;Guan, Liu, Ye & Yang, 2005) and infant formulas (Ferrer et al, 2000;Birlouez-Aragon et al, 2004;Birlouez-Aragon, Locquet, Louvent, Bouveresse & Stahl, 2005). However, studies on the effects of storage on the formation of fluorescent compounds in infant formulas (Ferrer, Alegría, Farré, Clemente & Calvo, 2005) and milks (Gliguem et al, 2005; Birlouez-Aragon, Sabat, Lutz, Leclère & Nicolas, 1999) are scarce, and there is a lack of reports on the formation of MR products in infant foods, as a consequence of either processing or storage.…”
Section: Measurements Of Fluorescence At Different Wavelengths or Thementioning
confidence: 99%
“…Indeed, Christensen et al [10] have used this method to predict riboflavin content of 42 yogurt samples, obtaining successful results and underlining the potential of the method to be utilised for rapid determination of riboflavin. This technique has also been used for the determination of lactulose and furosine in milks [30]. However, no research has investigated the feasibility of using front-face fluorescence spectroscopy to predict chemical parameters in cheese.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that front-face fluorescence spectroscopy can discriminate milk samples subjected to heat treatment from those subjected to homogenisation [13] and monitor structural changes occurring during milk coagulation [14,18,19] and cheese manufacture [20,32,33]. In addition, this technique has been used for the determination of lactulose and furosine in milks [28] and the evaluation of oxidative changes in processed cheese during storage [9,34,41]. Indeed, Wold et al [41] have demonstrated that fluorescence properties of riboflavin can be used to measure the degree of degradation of riboflavin in dairy products.…”
Section: Introductionmentioning
confidence: 99%